Litter Gender Composition and Sex Affect Maternal Behavior and DNA Methylation Levels of the Oprm1 Gene in Rat Offspring - Hao, Yanli; Huang, Wen; Nielsen, David A.; Kosten, Therese A. (Frontiers in Psychiatry, 2011)
The mu-opioid receptor is encoded by the Oprm1 gene and contributes to mother-infant behaviors. Rodent dams lick male pups more than female pups in the anogenital region. This behavior is linked to stress responsivity in the offspring that may be mediated by epigenetic changes. We hypothesized that maternal behavior may affect DNA methylation levels of the Oprm1 gene and show sex differences. To further explore sex differences in mother-pup behaviors and DNA methylation levels, we altered the litter gender composition (LGC) of rats. Litters were culled to 8 all male, all female, or 4 male/4 female pups on postnatal (PN) day 1. On PN4, 7, and 10, a dam was placed in a test cage with a pup for a 10-min period. Latency to pup contact was determined as were times spent licking the anogenital and other body regions of the pup. Frequencies of other behaviors were tabulated. On PN35, samples from various brain regions were obtained. DNA methylation at specific CpG sites in the Oprm1 promoter region were measured by direct sequencing of bisulfite treated DNA. LGC and sex interacted with day for latency to pup contact. Latencies were longest on PN4 for single-sex males and on PN10 for single-sex females. Dams licked male pups more than female pups in both the anogenital and other body areas. Sex differences were seen in other behaviors. LGC altered DNA methylation at specific CpG’s of Oprm1 in hippocampus with higher levels in single-sex rats. In nucleus accumbens, single-sex males showed hypermethylation levels, a trend seen in caudate-putamen. Results confirm and extend sex differences in maternal care with modest LGC effects. That both LGC and sex have enduring effects on DNA methylation of the Oprm1 gene in brain regions associated with addiction, stress regulation, motivation, and cognition may suggest one factor that contributes to gender differences in these behaviors.